DESIGN AND ANALYSIS OF BUS BODY SUPERSTRUCTURE - Reddy, D.Purushottam; ali, S.Sardar; Srikanth, D.; Mohanachari, JV. (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Buses are the major mode of public transportation. The design of the bus body depends largely upon the performance requirements under various types of loading, operating conditions and the road conditions. The structural design also varies on the basis of the passenger capacity, the types of usage, and the nature of operation: urban/rural, long run/city run etc. Based on above requirements the structural materials, the size and shape of the structural member, the joint designs etc., are selected. In India, most of the buses are designed and fabricated on the basis of past experience . The 3D model of bus body superstructure is prepared by using Pro E software and structure and modal analysis carried out by Ansys work bench. At present evaluating the strength and vibration in Bus Body Superstructure at different locations with normal static load. Finite Element modelling of a Bus body structure described for finding the analysis of vibration/stress levels at different locations of the vehicle. The stress, deformation are obtained for different materials of bus superstructure at cant rail and waist rail.